Assessing Social Impacts of Slum Displacement on Women’s Lives: A Case Study of three Resettlement Colonies in Delhi, India - Bajpai, Deeksha; Gautam, Upma (Kathmandu School of Law Review, 2018)
The mega-cities’ displacement often affects all in different ways but it goes economically, politically and socially beyond words to most vulnerable and marginalized groups of the population. Further, impoverishment and risks associated with resettlement can be felt more intensely on and by certain segments of the displaced population. Such projects have multiple and differential impacts, especially on women, men and children. Nonetheless, regardless of differences in caste, class, religion, or region, women everywhere bear the heavy brunt (in terms of tangible and intangible losses) of the forced move a lot more than the male members of their families. This very paper has projected a detailed study of similar courses on women of three major resettlement colonies of Bawana, Bhalsawa and TikriKhurd in Delhi, India.